STABILITAS EDIBLE FILM PATI SAGU (METROXYLON SAGU ROTTB.) ASETAT SELAMA PENYIMPANAN PADA BERBAGAI SUHU - Rosniyati Suwarda; Tun Tedja Irawadi; Prayoga Suryadarma; Indah Yuliasih (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
The degree of stability of starch-based edible films during storage varies greatly compared to synthetic films. This work aimed to study the effect of storage temperatures on the stability of sago starch acetate edible film during storage. Edible films produced by casting and storage at 5, 30 and 40 oC temperatures for 34 days. The observed characteristics were crystallinity, contact angle, physical, mechanical and barrier (WVTR) film properties. Sago starch acetate edible films presented lower relative crystallinity (10,10%) and highest contact angle (51,04o) when compared with native starch edible films. The results indicated that sago starch acetate edible films were relatively stable when stored at low (5 oC) and high (30 and 40 oC) temperatures. Storage temperatures did not affect physical properties (solubility, transparency) and mechanical (elongation at break / EAB) of sago starch acetate edible films except tensile strength (TS) and water vapor transmission rate (WVTR). TS values ​​increased at temperatures 30 and 40 oC and WVTR values ​​increased at temperature 30 oC. Changes in physical and mechanical properties occur at the beginning of storage, but then tend to be stable until the end of storage. Sago starch acetate edible films had low physical and mechanical characteristics, that was TS (2.25–4.90 MPa), elongation at break (29.65–89.62%), solubility (15.01–29.61%), transparency (0.91–1.87) and very low WVTR value (0.07–0.33 g/m2.hour) and Ea (-8.6E-04 kJ/mol). Sago starch acetate edible films had good physical and mechanical properties and resistant to moisture, can be used for applications as edible films and coatings for foods that contain high water content. Keywords: edible film, mechanical and physical properties, sago starch acetate, water vapor transmission rate